PERANCANGAN PRODUK PAI BUAH LAI DENGAN MENGGUNAKAN MODEL KANO DAN METODE QFD - Ainun Rif'ah; Farida Djumiati Sitania; Suwardi Gunawan (Jurnal Agritechno, 2020)
Lai is the original fruit of Borneo. Lai has the potential as a superior tropical fruit to accompany durian with its unique properties. Lai has yellow and orange flesh, fresh taste, and soft fragrant. The utilization of lai fruit is still not maximum, it can be seen that the fruit is only sold when the fruit is ripe and consumed directly without any processing innovation so that the selling value of the fruit is low and the shelf life is short. The purpose of this research is to design processed lai fruit into pie products according to consumer needs using the Kano Model and The Quality Function Deployment (QFD) Method at the product planning stage. Data collection was carried out by distributing Kano questionnaires and the level of importance questionnaires. Questionnaires were distributed to people who lived in Samarinda who have an age range between 20 to 30 years who have consumed pies and lai fruit. The Kano questionnaire was used to determine the characteristics required by consumers. While the importance level questionnaire was used to obtain data on the level of consumer interest. The Kano model and Quality Function Development (QFD) Method were used to process the data in the product planning stage by compiling the House of Quality (HOQ). Based on data processing by using The Kano Model, obtained there were 12 statements classified as one dimensional, 2 statements classified as must be, and 7 statements classified as indifferent. There were 14 statements related to consumer’s characteristics classified into Quality Function Development (QFD), they were included in the category one dimensional and must be. Based on data processing by using Quality Function Development (QFD), obtained 12 technical parameters which could be developed based on consumers’ need. The marketable design of the Lai pie product that is preferred by consumers is the one with dough mixing process, baking process, and quality control process.Those three technical parameters are closely related to the five priorities of consumers’ characteristics. The dough mixing process is associated with the existed genuine taste of Lai and the smoothness of Lai vla (custard). The baking process is affiliated with the crispiness of Lai pie crust and its delicious aroma. The Quality Control process is related to product sorting before it is marketed.